A New Taxon of Salvia (Lamiaceae) From Türki̇Ye (Bangladesh Journal of Plant Taxonomy, 2022)
Salvia divaricata Montbret & Aucher ex Benth. subsp. artvinense Eminagaoglu, Ozcan & Akyıldırım is described as a new endemic subspecies from Ardanuç (Artvin, Türkiye). It is related to Salvia divaricata Montbret & Aucher ex Benth. and S. tomentosa Mill. from which it differs in stem, leaf characters and flower color and numbers. A key is given to distinguish the new subspecies from the other species in the genus Salvia. Morphology, stem, petiole and leaf anatomy, and nutlet micromorphology were investigated. Nearly rounded stem, hemispherical petiole, bifacial leaf with diacytic stomata, and ovoid to rotund nutlet with glabrous and distinctly rough to protuberances ornamentation were determined for this subspecies. Taxonomic interpretations of the new subspecies are given using morphological, anatomical and phylogenetic analyses.Bangladesh J. Plant Taxon. 29(2): 167-181, 2022 (December)